Comparison of greywater treatment processes with coagulating agent and oxidizer - Ungvári, Csaba; Izbékiné Sazabolcsik, Andrea; Lós, Réka; Bodnár, Ildikó (International Journal of Engineering and Management Sciences, 2019)
In our research synthetically produced greywater samples were treated with oxidative and coagulating agents after pre-treatment them by filtration on various filters. We characterised the quality of greywater samples with several parameters. We investigated these parameters on the untreated, pre-treated, and treated samples as well. We evaluated the efficiency of the treatments by measuring the characteristic parameters. The greywater treatment is a very important and effective opportunity for the reasonable freshwater usage. This type of treated water can be suitable for toilet flushing or irrigation. There are a several methods known from the literatures to preparation the greywater samples to reuse. We compared two of these methods in this article.